2020
DOI: 10.1016/j.jfca.2019.103309
|View full text |Cite
|
Sign up to set email alerts
|

Total folate in West African cereal-based fermented foods: Bioaccessibility and influence of processing

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 49 publications
0
18
1
Order By: Relevance
“…Such a fortification is of great importance for specific population groups that follow special types of dietary regimes, either by choice (e.g., vegans) or due to cultural habits, religious beliefs, and lack of other available food sources (developing countries). It is worth mentioning that in some African countries, porridges made of cereals can complement breastfeeding [51,52].…”
Section: Vitaminsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a fortification is of great importance for specific population groups that follow special types of dietary regimes, either by choice (e.g., vegans) or due to cultural habits, religious beliefs, and lack of other available food sources (developing countries). It is worth mentioning that in some African countries, porridges made of cereals can complement breastfeeding [51,52].…”
Section: Vitaminsmentioning
confidence: 99%
“…The used strains were isolated from durum wheat flour and have been characterized as riboflavin-overproducing microorganisms according to in vitro tests with synthetic media [55]. More recently, Bationo et al [52] reported that processing steps like debranning, soaking, and wet-milling may cause a decrease in cereals' folate content by up to 60%, while on the contrary, fermentation increased folate's concentration by up to 27%. Various fermented cereal-based foods were studied (fritters, dumplings, porridges, and gelatinized doughs, made from sorghum, corn, or pearl millet) and their estimated folate bioaccessibility ranged from 23% to 81% using an in vitro digestion model.…”
Section: Vitaminsmentioning
confidence: 99%
“…Another hypothesis is that the processing method could affect the bioaccessibility of folate by modifying the structure of the food. Bationo et al 18 studied the bioaccessibility of folate in seven types of African cereal-based products and found that those with dense structures had the highest folate bioaccessibility (57-81%). Moreover, a recent report by Hiolle et al 19 stated that the release of added folic acid during the gastric phase was faster for biscuit and sponge cake than for custard and pudding, although they were made from the same materials.…”
Section: Introductionmentioning
confidence: 99%
“… Muyanja et al, 2003 ; Lei and Jakobsen, 2004 ; Yousif et al, 2005 ; Vieira-Dalodé et al, 2007 ; Assohoun et al, 2012 ; Oguntoyinbo and Narbad, 2012 ; Greppi et al, 2013 ; Sanni and Adesulu, 2013 ; Adesulu-Dahunsi et al, 2017a ; Bationo et al, 2019 ; Pswarayi and Ganzle, 2019 . …”
Section: Predominance Of Lactobacillus Spp During ...mentioning
confidence: 99%